The Influence of Creative Products and Entrepreneurship Subjects on Entrepreneurial Interests of Fashion Design Students at Citra Harapan Vocational School - Siregar, Wildah Nur; Ismayuni, Tri Utari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine the influence of the Creative Product and Entrepreneurship subjects on students' entrepreneurial interest in the Fashion Design Department at SMK Citra Harapan Jaya. The research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 30 students and practical assessments conducted by teachers. The data were analyzed using multiple linear regression with the assistance of SPSS version 30, along with prerequisite tests including normality, linearity, and multicollinearity tests.The analysis results indicate that the Creative Product and Entrepreneurship subjects simultaneously have a significant influence on students’ entrepreneurial interest, with an Fcount value of 428.798 and an Ftable value of 3.35 at a 5% significance level (α = 0.05). Since Fcount > Ftable (428.798 > 3.35), this indicates a very strong influence. These findings confirm that practice-based learning in the Creative Product and Entrepreneurship (PKK) subject is effective in fostering students’ interest in becoming entrepreneurs, particularly in the field of fashion design.